The design and implementation of a wireless flood monitoring system - Yasir, Hashim; Abdul Hafiz, Mohd Idzha; Jabbar, Waheb A. (UTeM, 2018)
Floods and excessive rainfall are unavoidable phenomena that can cause massive loss of people's lives and destruction of infrastructure. Recently, the impact of floods on human lives can be avoided by the presence of flood monitoring systems (FMS). Although, there are many systems widely in practice by disaster management agencies in monitoring flood level. Most of these systems are very costly and sophisticated to be used and maintained. Furthermore, most of the conventional flood gates in water canals are manually-operated, and suffer from the lack of real time monitoring of water levels which might lead to overflow in the canals and flash floods. Therefore, in this paper, we have designed and fabricated an innovative, cost effective, and user-friendly water level measurement system. The developed system exploits an ultrasonic sensor with Arduino microcontroller to measure the water level and identify the situation whether it is safe, cautious or dangerous based on predefined levels. The implemented prototype can act as a beacon for alerting individuals and/or authorities separately via SMS using GSM module or Bluetooth. Our system has been tested as an individual unit and the results were very promising. Our system can monitor the water level accurately and show visual alerts using LED, in addition to send messages over Bluetooth and Cellular networks. In the future, we are going to implement multiple units of the fabricated system to enable them to work as wireless network for flood monitoring.